Musical Ability and Interpersonal Intelligence in The Late Childhood Period - Hana Permata Heldisari (Universitas Negeri Medan, 2020)
Learning to adjust to peers and develop attitudes towards social groups and institutions is one of the developmental tasks of late childhood. Musical abilities present as innate and function since childhood.Associated with two things namely interpersonal intelligence and musical abilities, both are being developed in late childhood. This study aims to determine whether there is a relationship between musical ability and interpersonal intelligence in the late childhood period. This research uses quantitative research method with the type of correlation. The population of this research was all students in grade 1-3 of Pangen Gudang Purworejo State Elementary School with a total of 107 people. The sample in this study was taken proportionally stratified random sampling, with a sample size of 32 people. The data collection was carried out by using questionnaire and test techniques. The data analysis uses product moment correlation, with musical ability as the independent variable and interpersonal intelligence as the dependent variable. The result showed that there was a strong and significant positive relationship between musical abilities and interpersonal intelligence in children during late childhood period. This evidence was obtained by r count > r table (0.643> 0.349) at 5% significance level. This means that the higher the musical ability, the higher the interpersonal intelligence students will have.